Implementation of Digital Systems in the F&B Department: Enhancing Guest Satisfaction and Service Efficiency: Implementasi Sistem Digital di Departemen F&B: Meningkatkan Kepuasan Tamu dan Efisiensi Layanan - Suharto, Bambang; Medina, Fadita Dwi; Ardianto, Kiara Dwiva (Institut Pariwisata dan Bisnis Internasional, 2024)
This paper will discuss the importance of digital system innovation in increasing guest satisfaction and service efficiency in the Food and Beverage (F&B) department in the hospitality industry. The purpose of this article is to outline an overview of the various digital technologies that have been adopted in the F&B Department, as well as their impact on guest satisfaction and operational performance. The method used is a qualitative descriptive approach. Various studies and case studies are analyzed to understand how the implementation of digital systems such as restaurant management software, online ordering applications, and Internet of Things (IoT) technologies has impacted various aspects of operations, from inventory management to service provision.